I want to show that if $f:(a,b)\to \mathbb R$ is a strictly monotone function and if $x_0\in (a,b)$ such that there exist two sequences $(a_n)$ and $(b_n)$ with $a_n<x_0<b_n$ and $\lim\limits_{n\to \infty}(f(b_n)-f(a_n))=0$, then $f$ is continuous at $x_0$.

By monotonicity we can say that $\lim\limits_{n\to \infty}f(a_n)=f(x_0)=\lim\limits_{n\to \infty}f(b_n)$. Let $(x_n)$ be a sequence in $(a,b)$ such that $x_n\to x$. Here I got stuck. How to show that $f(x_n)\to f(x_0)$? Please help!


1 Answer 1


We may assume that $f$ is strictly increasing. (Otherwise, replace $f$ with $-f$.)

Let $\epsilon > 0$. Since $\lim_{n \to \infty} (f(b_n) - f(a_n)) = 0$, there is some $N$ such that $|f(b_N) - f(a_N)| < \epsilon$.

As $a_N < x_0 < b_N$ and $x_n \to x_0$, there is some $M$ such that $a_N < x_n < b_N$ for all $n \geq M$.

Since $f$ is strictly increasing, we have the inequalities $$f(a_N) < f(x_0) < f(b_N) \qquad (1)$$ and, for $n \geq M$, $$f(a_N) < f(x_n) < f(b_N) \qquad (2)$$ Since (1) is equivalent to $$-f(b_N) < -f(x_0) < -f(a_N) \qquad (3)$$ we can add (2) and (3) to obtain $$-(f(b_N) - f(a_N)) < f(x_n) - f(x_0) < f(b_N) - f(a_N)$$ which is the same as $$|f(x_n) - f(x_0)| < f(b_N) - f(a_N) < \epsilon$$ which holds for all $n \geq M$. As $\epsilon > 0$ was arbitrary, we conclude that $f(x_n) \to f(x_0)$ as desired.

  • 2
    $\begingroup$ By the way, we don't really need $f$ to be strictly monotone. Nonstrict monotonicity is sufficient. In that case, all of the $<$ starting at the line labeled (1) become $\leq$, but that won't affect the outcome. $\endgroup$
    – user169852
    Aug 25, 2016 at 17:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.